Pengaruh Model Kulit Bumi terhadap Gelombang ScS dan ScS-ScS - Bagus Jaya Santosa (Jurnal Fisika dan Aplikasinya, 2009)
True median cleft lip is an anomaly accounting for ∼0.1% to 0.7% of all cleft lip and palate cases, and its co-occurrence with multispectral bilateral ocular anomalies remains undocumented. The authors report a unique case of true median cleft lip concomitantly associated with left anophthalmia-characterized by the complete absence of the globe-and right morning glory syndrome, a rare congenital optic disc anomaly featuring a deeply excavated papilla with a central plug of white glial tissue. The patient, a male infant, presented with a midline upper lip fissure and an intact brain parenchyma. At 6 months of age, surgical repair of the lip and excision of an associated maxillary alveolar cartilaginous hamartoma were performed. This represents the first reported case globally demonstrating this specific triad, providing critical embryological insights into early, continuous morphogenetic disruptions affecting both midline facial and ocular co-development.